2022
DOI: 10.1002/pul2.12093
|View full text |Cite
|
Sign up to set email alerts
|

Association of residual pulmonary hypertension with survival after pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension

Abstract: This study investigated whether residual pulmonary hypertension (PH), defined as early postoperative mean pulmonary artery pressure (mPAP) of ≥30 mmHg, after undergoing pulmonary endarterectomy (PEA) for chronic thromboembolic pulmonary hypertension (CTEPH) was associated with longterm survival. All patients who underwent PEA for CTEPH at two Scandinavian centers were included in this study. Baseline characteristics and vital statuses were obtained from patient charts and national health-data registers. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
2
6
1
Order By: Relevance
“…In other centers, early mortality was observed to be higher in women undergoing PEA as reported from a Scandinavian observational cohort study of 444 patients. Long-term survival analysis suggested however, that the observed survival in men was close to the expected survival in the matched general population, whereas survival in women deviated notably from the matched general population [4]. This in contrast to the results of an analysis of sex-specific differences in the European CTEPH registry showing that women had a better long-term survival, irrespective of the performance or not of PEA [5].…”
contrasting
confidence: 61%
“…In other centers, early mortality was observed to be higher in women undergoing PEA as reported from a Scandinavian observational cohort study of 444 patients. Long-term survival analysis suggested however, that the observed survival in men was close to the expected survival in the matched general population, whereas survival in women deviated notably from the matched general population [4]. This in contrast to the results of an analysis of sex-specific differences in the European CTEPH registry showing that women had a better long-term survival, irrespective of the performance or not of PEA [5].…”
contrasting
confidence: 61%
“…Other studies have demonstrated an association between residual PH and long‐term survival after PEA for CTEPH. 26 Furthermore, CAMPHOR scores were higher in the post‐PEA population than in propensity score‐matched patients with CTEPH who did not undergo surgery. In our study, CAMPHOR scores were obtained 5.9 years (range: 0.4–20 years) after PEA and were very similar to those in the UK cohort.…”
Section: Discussionmentioning
confidence: 95%
“…The correlation between residual PH and short- and long-term post-operative outcomes is also a matter of debate: a prospective study from the Cambridge group showed that the 5-year survival rate did not differ between patients with a post-operative mPAP of <30 mmHg and those with values of ≥30 mmHg [ 45 ]. Recently, some authors found a strong and clinically relevant association between residual PH and long-term survival after PEA [ 46 ]. Again, the recent ERS statement on CTEPH has acknowledged that significant residual PH is a challenge to treat early post-operatively and is the most common cause of in-hospital mortality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%